2022
DOI: 10.5114/ada.2022.115888
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vascular endothelial growth factor on neutrophil activation in asthmatics

Abstract: Introduction Asthma is a complex syndrome associated with heterogeneity in the type of inflammation that modulates airway hyperresponsiveness and remodelling. Airway inflammation with neutrophils, cytokines like vascular endothelial growth factor (VEGF) and various gene polymorphisms might be relevant for asthma pathogenesis. Aim To investigate the expression of CD69 and CD11b markers on peripheral neutrophils after VEGF in vitro stimulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Interestingly, previously it has been shown that increased VEGF serum concentration applies to patients with asthma, especially with irreversible bronchoconstriction [33]. Other papers suggested basophils or neutrophils VEGF-activation in asthmatics [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previously it has been shown that increased VEGF serum concentration applies to patients with asthma, especially with irreversible bronchoconstriction [33]. Other papers suggested basophils or neutrophils VEGF-activation in asthmatics [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK/Akt activation activates factors such as VEGF, which promotes the proliferation of airway structural cells, including alveolar epithelial cells, bronchial endothelial cells, fbroblasts/myofbroblasts, and bronchial smooth muscle cells, can contribute to infammation and angiogenesis in various pulmonary infammatory diseases, making the lumen narrower and participating in airway remodeling [46,47]. Moreover, VEGF accelerated M2 macrophage infltration and disrupted the airway epithelial barrier in lung tissues of asthmatic animals [48][49][50][51]. Emerging evidence also displayed that VEGF has associations with thromboembolism and tissue injury/repair in COVID-19 and viral infection, indicating the promotion of secondary airway infammation [52][53][54].…”
Section: Discussionmentioning
confidence: 99%